2022
DOI: 10.1038/s41375-021-01492-y
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA for the detection of emerging treatment failure in relapsed/ refractory multiple myeloma

Abstract: Interrogation of cell-free DNA (cfDNA) represents an emerging approach to non-invasively estimate disease burden in multiple myeloma (MM). Here, we examined low-pass whole genome sequencing (LPWGS) of cfDNA for its predictive value in relapsed/refractory MM (RRMM). We observed that cfDNA positivity, defined as ≥10% tumor fraction by LPWGS, was associated with significantly shorter progression-free survival (PFS) in an exploratory test cohort of 16 patients who were actively treated on diverse regimens. We pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Mithraprabhu et al ( 16 ) found that patients with higher cfDNA levels had significantly poorer overall survival, and that reductions in cfDNA levels were associated with improvement after several days of chemotherapy cycles. Waldschmidt et al ( 17 ) prospectively enrolled 86 blood samples from 45 MM patients treated with drugs such as pomalidomide, bortezomib, and dexamethasone in a phase II clinical trial. After two cycles of treatment, higher levels of cfDNA were found to be associated with worse PFS (1.6 vs. 17.6 months).…”
Section: Discussionmentioning
confidence: 99%
“…Mithraprabhu et al ( 16 ) found that patients with higher cfDNA levels had significantly poorer overall survival, and that reductions in cfDNA levels were associated with improvement after several days of chemotherapy cycles. Waldschmidt et al ( 17 ) prospectively enrolled 86 blood samples from 45 MM patients treated with drugs such as pomalidomide, bortezomib, and dexamethasone in a phase II clinical trial. After two cycles of treatment, higher levels of cfDNA were found to be associated with worse PFS (1.6 vs. 17.6 months).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ctDNA level only showed a conditional correlation with myeloma cell infiltration in the BM. Although some studies found that patients with a high ctDNA level had more BM infiltrations [47,48,57,73], no quantificational correlation was found between the VAF of tumor-related mutations in cfDNA and BM MM cell infiltration [10], which could be explained by BM heterogeneity and the presence of EM lesions. According to a previous report, patients with short progression-free survival (PFS) and high tumor burden by cfDNA were observed to have inconsistently low BM infiltration.…”
Section: Disease Burden Assessmentmentioning
confidence: 91%
“…A previous study found that the TF in cfDNA from MM was 4.5 times higher than that in cfDNA from MGUS and SMM [56]. The cfDNA levels were observed to be significant predictors of clinical scores or markers of high disease burden, including advanced ISS stage [9,57,73] and R-ISS stage [46,73], elevated levels of LDH [3,9,47,73] and β2-MG in serum [9], more EM disease in positron emission tomography-computed tomography (PET-CT) [47,74], or osteolytic lesions [48,74]. Most patients showed a positive correlation between the frequencies and VAF of mutations [57,73,75,76], the TF based on CNAs [3,49,74,76], and the frequencies of MM clones (Ig rearrangements) [36] in paired myeloma cells in the BM and cfDNA.…”
Section: Disease Burden Assessmentmentioning
confidence: 93%
See 1 more Smart Citation
“…In the case of MM, ctDNA burden correlates with higher 70-GEP and prognosis, with patients with higher burden having worse PFS and OS ( 41 ). Furthermore, it has been proposed as a tool to detect treatment failure and subsequent relapse in the RRMM setting ( 42 ). As mentioned before, the integration of SNV’s, translocation, and copy number changes into defined molecular subgroups of SMM improve the performance of 2/20/20 model ( 34 ), but will lack of widespread access to this technology remains a limitation.…”
Section: Future Biomarkers In Smm and Multiple Myelomamentioning
confidence: 99%